Human leukocyte antigen B polymorphism and association between HLA‐B27 and endoplasmic reticulum aminopeptidase 1 rs30187 SNP in patients with ankylosing spondylitis in Bangladesh. Issue 1 (15th February 2022) - Sajib, Md Kamrul H.; Ahmed, Shamim; Haq, Syed A.; Choudhury, Minhaj R.; Uddin, Mohammed; Uddin, Furkan; Khan, Muhammad S. A.; Zaman, Mohammad M.
Abstract: Objectives: To determine the association of Human leukocyte antigen B (HLA‑B) alleles with ankylosing spondylitis and the allelic association of HLA‐B27 with endoplasmic reticulum aminopeptidase 1 ( ERAP1 ) single‐nucleotide polymorphism (SNP) rs30187 in patients with ankylosing spondylitis (AS). Methods: We studied 48 consecutively enrolled well‐defined AS patients and 48 healthy controls recruited from the outpatient clinic of the rheumatology department of Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh. To genotype HLA‐B alleles from peripheral blood DNA, we designed sequence‐specific primers for polymerase chain reaction. Sanger's sequencing method was used to detect the ERAP1 rs30187 SNP. The HLA‐B allele distributions were compared between cases and controls. To infer an allelic association between HLA‐B27 and ERAP1, allele distributions from both loci were compared using cross‐tabulations. Chi‐squared test or Fisher's exact test was used to quantify the association, and their strength of association was tested by odds ratio (OR) with 95% confidence interval (CI). Results: The frequency of HLA‐B27 was found to be higher in AS patients (60.4%) than in healthy controls (8.3%). HLA‐B27 allele had an OR of 16.8 (95% CI = 5.2–54.4) for the development of AS. Overall, 4% of AS patients had both HLA‐B27 and HLA‐B40. No significant association was found between ERAP1 rs30187 SNP and HLA‐B27 in patients with AS (OR = 1.7, 95% CI = 0.5–5.6). Conclusions: HLA‐B27 was significantly associated with AS in patients in Bangladesh. However, no association between ERAP1 rs30187 SNP and HLA‐B27 was observed. Abstract : Key points: HLA‐B27 was more frequently found in AS patients (60.4%) than in controls (8.3%). The combination of HLA‐B27 and HLA‐B60 was only found in AS patients. No association between ERAP1 SNP rs30187 and HLA‐B27 was observed in Bangladeshi AS patients. First HLA‐B27 association in Bangladesh. Limitation: Single tertiary level hospital‐based study.